Effect of Intermediate Stiffeners on the Behaviors of Partially Concrete Encased Steel Beams - Cheng-Cheng Chen; Teguh Sudibyo (Advances in Civil Engineering)
Partially concrete encased steel (PE) beams are composite steel beams and concrete elements that present several advantages, such as higher fire resistant, higher flexural capacity, and higher lateral torsional buckling resistant compared to bare steel beams. This paper reports an experimental study of eight PE beams under cyclic loading. The effectiveness of intermediate stiffeners, such as midspan stiffener and plastic hinge zone stiffener, in enhancing composite action and ductility of the PE beams was studied. The ductility performance of PE beams using strengthened beam-to-column connection and weakened beam-to-column connection was also investigated. The test results show that the plastic hinge zone stiffener performed well and has the potential to replace shear connectors. Strengthened and weakened beam-to-column connections can be implemented in PE beams to enhance the ductility of the PE beams; with the details of both strengthened and weakened beam-to-column connections determined by bare steel shape instead of the whole section. In addition, the suggestions to prevent premature failure of weakened beam-to-column connection were provide.